Determinant Factors of Enterprise Value from PBV and Tobin’s Q Perspectives - Martini, Martini (STMIK Widya Cipta Dharma, 2024)
The mining sector is one of the key industries contributing to economic growth and sustainable development globally. Despite its significant role, this industry faces challenges in managing various negative impacts that can harm the environment and society. One common issue is conflicts with local communities, often arising from differing perspectives or perceptions regarding natural resource management. Investors evaluate the success of companies in this sector based on enterprise value (EV), which can be measured using metrics such as Price-to-Book Value (PBV) or Tobin's Q. This study aims to analyze the effects of stock prices, profitability, and debt policies on enterprise value, assessed through PBV and Tobin's Q, in mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The data analysis method used in this research is multiple linear regression. The results indicate that stock prices, profitability, and debt policies have a positive and significant effect on enterprise value when measured using PBV. In contrast, when enterprise value is measured using Tobin's Q, stock prices and debt policies show a positive and significant influence, while profitability does not significantly affect enterprise value.